Cathode catalyst selection for enhancing oxygen reduction reactions of microbial fuel cells: COF-300@NiAl-LDH/GO and Ti3AlC2/NiCoAl-LDH. (29th April 2022) - Chen, Junfeng; Yang, Jiaqi; Wang, Xuemei; Yang, Daoxin; Yang, Muyi; Tian, Jiarui; Tao, Ran; Wang, Yongle; Wei, Qingying; Wang, Renjun; Yang, Yuewei; Liu, Yanyan
Abstract: In this study, a cathode catalyst for microbial fuel cells (MFCs) was successfully prepared by a simple step-by-step hydrothermal method. Graphene oxide (GO) and layered double hydroxide (LDH) composite substrate and three-dimensional covalent organic framework materials (COF-300) grown vertically on the surface were observed. (003), (006), (012), (018), (110) were the obvious crystal plane of the composite COF-300@NiAl-LDH/GO. C, O, N, Ni, Na, Al and other elements existed on the surface of the composite. The maximum power density produced by COF-300@NiAl-LDH/GO-MFC was 481.69 mW/m 2, which was 1.22 times of Ti3 AlC2 /NiCoAl-LDH-MFC (393.82 mW/m 2 ) and 2.21 times of Ti3 AlC2 -MFC (217.73 mW/m 2 ). The maximum voltage of COF-300@NiAl-LDH/GO-MFC was 518 mV and it could remain stable within 8 days. GO was used as the substrate to improve the conductivity; LDH was used to enhance the catalytic activity and electron transfer rate; The three-dimensional bulk COF-300 attached to the surface enhanced the surface area and catalytic properties; The above jointly promoted oxygen reduction reaction of cathode, so as to improve MFC performances. Graphical abstract: Image 1 Highlights: COF-300@NiAl-LDH/GO was perfectly synthesized by step-by-step feeding method. COF-300@NiAl-LDH/GO was multiple active sites, high surface area and stability. Maximum power density of COF-300@NiAl-LDH/GO-MFC was 481.69 mW/m 2 .